Transient photovoltage study of organic solar cells based on small molecules - Ee, Nicholas Wei-Kang (2009)
As Earth’s resources are being depleted, the organic solar cell is gathering much attention as an inexpensive alternative for renewable energy. Since the construction of the first inorganic solar cell in 1883, the solar cell has seen vast improvements to this date. With the different architectures available for organic solar cells, an investigation to study the fundamental phenomena underlying the performance of these devices was undertaken. In this study, transient photovoltage technique was employed to observe how the device was affected by the absence and the presence of an external bias. The results have shown how long term photovoltage as well as polarity changes were affected by external fields as well as the innate properties of the device. Also, through the use of Time-Of-Flight technique, an estimation of the mobility of the charge carriers within the organic solar cell was made possible. Included in this study will be descriptions of other techniques such as DI-SCLC and CELIV along with their application in finding the mobility of charge carriers for future reference. Through the transient photovoltage study, certain insights have surfaced to reveal how the performance of the organic solar cell could be affected by Donor / Acceptor interface and ITO interactions. These findings could eventually lead to an improvement of the device performance and in the future, possibly lead to the production of a commercially viable organic solar cell.